What's for breakfast? - Cazet, Denys (New York : Roaring Brook Press, 2018)
"Wake up!" says Rufus, a large and very hungry owl. "It's time to catch the fearsome mouse. I'm in a mood for a bowl of mouse soup for breakfast." Pip, who's better at sleeping than swooping, leaps from the nest and lands right on top of that fearsome mouse whose name, he learns, is Theodore. Is it time for breakfast... or friendship? Find out in this clever and classic picture book about two owls, a mouse, a banana, and an unlikely friendship. -- from Amazon.
"A Neal Porter book."
Keywords: Owls -- Juvenile fiction; Mice -- Juvenile fiction; Animal behavior -- Juvenile fiction; Friendship -- Juvenile fiction; Picture books